IMPLEMENTATION OF CRIMINAL SANCTIONS AGAINST COMPANIES THAT DO NOT PAY BPJS EMPLOYMENT DUES (Study : Putusan Pengadilan Negeri Sumedang Number 109/Pid.Sus/2017/PN.Smd) - Isnaini Apri Dawati; Lusia Indrastuti; Endang Yuliana Susilowati (Wacana Hukum, 2021)
This research aims to open wide to the public, especially the workforce about the implementation of laws related to employment and provide examples in relation to the implementation of labor protections whose rights have been lost, so that in the future workers who experience similar things can act to fight for their rights and for companies, this can be a reminder to always carry out their obligations. The method of writing in this study uses normative juridical, by producing findings that violations of the law related to employment often occur such as workers who cannot claim the employment social security program as labor rights as a result of the company's negligence, namely the non-payment of dues by the company to BPJS Employment, enforcement related to it has been done even though the inplementation of the criminal sanctions is still relatively few but there has been progress reflected in the use of the article to ensnare one of the companies that collect but do not deposit dues in the Sumedang State Court in Decision No. 109 / Pid.Sus / 2017 / Pn.Smd, so this becomes an example that labor is very guaranteed by the state.